Primary malignant melanoma of the oesophagus with a left atrial metastasis. - Chello, M (1993)
A 75 year old man with an eight month history of dysphagia and weight loss underwent pericardiocentesis for a massive pericardial effusion. The echocardiogram showed a mass in the left atrium, and computed tomography also showed distal oesophageal narrowing, which was found to be due to a malignant melanoma. The left atrial mass, investigated by immunoscintigraphy with technetium-99m labelled monoclonal antibody, was diagnosed as metastatic melanoma. This represents a rare case of primary oesophageal melanoma with left atrial metastasis.